Development and developmental potential of cortical thymic epithelial cells. Issue 1 (May 2016) - Ohigashi, Izumi; Kozai, Mina; Takahama, Yousuke
Summary: The thymic cortex provides a microenvironment for the development and positive selection of immature T cells. Cortical thymic epithelial cells (cTECs), which structurally and functionally support the thymic cortical microenvironment, originate from endodermal epithelial progenitors that arise in the third pharyngeal pouch. Recent studies have revealed that thymic epithelial progenitors pass through a stage where the cells express cTEC‐associated molecules prior to lineage separation into cTECs and medullary TECs (mTECs). Here, we review the molecular signatures of cTECs and highlight the development and developmental potential of cTECs.